Unlocking the Synergy: Artificial Intelligence and (old and new) Human Rights (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Artificial intelligence (AI) deeply and pervasively impacts our lives. In this short paper, I propose two lines of thoughts aimed at updating the catalog of human rights in light of the potential and risks of AI (mainly Machine Learning). The first considers the adaptation of certain traditional principles (informed consent and non-discrimination) to the challenges posed by AI. The second covers four new rights, built upon the specific characteristics of AI systems, with the aim of effectively addressing AI pros and cons.
Keywords: Artificial intelligence; AI act; fundamental rights; informed consent; non-discrimination